Analisis Permintaan Modal Kerja Usaha Mikro Pada Masa Pandemi Covid-19 Dalam Prespektif Permintaan Islam - Maulana Firdaus Firdaus; Lilik Rahmawati Rahmawati; Zuhrotun Nisa Nisa (Islamic Economics Journal, 2022)
One of the most crucial tools in starting a business is working cash. The Covid-19 Pandemic has been going on since the fourth quarter of 2019, and in the first quarter of 2020, things got so bad that small business owners couldn't raise enough money to keep their operations going. Own capital, money from investment funds, and working capital from banks make up the business's three sources of capital. Working capital from banks refers to funds obtained from banks in the form of financing at Islamic or credit at conventional banks. Economic conditions have improved across a number of industries as a result of the Covid-19 pandemic, which is starting to be under control. In this situation, the government offers a wide range of choices, from restructuring to the provision of new working capital for the microeconomic sector, to sustain economic circumstances so that they can quickly recover. Micro-scale business conditions have quickly improved as a result of the significant number of requests for working capital that financial institutions have received during this pandemic. Lower middle class or MSME entrepreneurs develop a wide range of products that can be offered on the market. Therefore, the goal of this essay is to examine the demand for working capital from an Islamic perspective during the Covid-19 pandemic. The descriptive qualitative approach is used in this research procedure. The findings of this study investigate, from the viewpoint of Islamic demand, the rising need for working capital for microbusinesses during the Covid-19 pandemic.